(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Healthcare is an ever-changing industry and signs show that this will most likely be the casefor many years to come. In order to have healthcare, companies must have facilities in which to providesaid care. This paper will focus on those facilities and what it takes to keep them operating at anoptimum state. Facilities management is a quite broad topic when looking at any industry but when itcomes to the facilities required to provide patient care the spectrum is mind boggling. Healthcarefacilities must have people to maintain them. These people are required to be knowledgeable in manyareas including but not limited to maintenance and construction activities. Employees in the facilitiesmanagement field are required to be trained in many fields including electrical, mechanical, plumbing,HVAC, and a host of other specialized areas. This paper will elaborate on the detailed training thatfacilities employees must complete in order to keep up with changes in the field.